Intellectual functioning in survivors of extremely low birthweight: Cognitive outcomes in childhood and adolescence. Issue 3 (22nd February 2023) - Mathewson, K. J.; Saigal, S.; Van Lieshout, R. J.; Schmidt, L. A.
Abstract: Background: Infants born at extremely low birthweight (ELBW: ≤1000 g) are vulnerable to intellectual disabilities, but the factors that may distinguish between ELBW survivors with and without these impairments are not well understood. In this study, prospective associations between neonatal factors and functional outcomes in childhood and adolescence were compared in ELBW survivors with and without borderline intellectual functioning (BIF). Methods: Borderline intellectual functioning was defined by IQ < 85, assessed at 8 years. Among 146 ELBW survivors, 48 (33%) had IQ scores under 85, and 98 (67%) had scores equal to or over 85. Group differences in demographic and risk factors were assessed via t ‐test, chi‐squared analysis or non‐parametric tests. Neonatal factors that differed between ELBW groups were tested for association with adaptive behaviour assessed at age 5 years, and reading and arithmetic skills assessed at ages 8 and 15 years, using hierarchical regression models. Results: Extremely low birthweight survivors with BIF had significantly lower birthweights than ELBW survivors without BIF (790 vs. 855 g, P <  0.01) and were more likely to be born to mothers with lower socioeconomic status (SES) (78% vs. 48%, P  < 0.01). These ELBW survivors also were more likely to be diagnosed with significant neurosensory impairment (NSI; 35% vs. 19%, P <  0.04), experienced more bronchopulmonary dysplasia (56% vs. 38%, P <  0.04), received more days of respiratory support (median 33 vs. 14 days, P <  0.01) and remained in hospital for longer periods (median 81 vs. 63 days, P <  0.03). Birthweight, familial SES, NSI and duration of respiratory support were significant predictors for one or more outcomes. Across groups, lower familial SES was associated with lower academic scores ( P s  <  0.05), and NSI predicted lower adaptive functioning ( P s  <  0.001). Other associations were moderated by group: among ELBW survivors with BIF, heavier birthweights predicted better arithmetic skills, the presence of NSI was associated with poorer arithmetic skills and more ventilation days predicted poorer reading skills. Conclusions: At birth, ELBW survivors with BIF faced more physiological and social disadvantages and required more medical intervention than their ELBW peers without BIF. Smaller birth size, NSI burden and prolonged neonatal ventilatory support displayed gradients of risk for childhood and adolescent academic outcomes across groups. Whereas academic performance in ELBW survivors with BIF was sensitive to variation in birth size, NSI or ventilation days, ELBW survivors without BIF attained thresholds of intellectual ability that were sufficient to support higher levels of academic performance at both ages, regardless of their status on these factors. The findings are discussed in relation to Zigler's developmental theory of intellectual disability.